Analisis Strategi Mempertahankan Pengungkapan Kualitas Laporan Keuangan Pemerintah Daerah Provinsi Sumsel Yang Meraih Opini Wajar Tanpa Pengecualian Pada Dinas Pengelolaan Sumber Daya Air Provinsi Sumsel - Mawardah, Arbainah; Noviardy, Andrian (CV. ITTC INDONESIA, 2024)
Research background/Problem: The goodness of the South Sumatra Province regional government's financial reports which have been audited by the Financial Audit Agency (BPK) is seen from 2014 to the present, resulting in an unqualified audit opinion Research objective: What strategies are carried out to assist the disclosures produced in Regional Government Financial Reports that receive an Unqualified Opinion in South Sumatra Province, which are carried out at one of the regional apparatus organizations, namely the South Sumatra Province Water Resources Management Service. Research method: using descriptive qualitative research methods through interviews, observation and documentation with reference to Rangkuti Theory, namely SWOT analysis. research results: Findings obtained through interviews conducted, the author in this research identified important strategies used by the Water Resources Management Service in maintaining good quality financial reports, which have been prepared using SWOT analysis, there are three strategies, namely the use of applications SIPD, reconciliation of monthly financial reports and training and testing of human resource capabilities. Conclusion: Although these findings reveal strengths, there are still several limitations which become weaknesses, namely lack of supervision for employee compliance with regulations, difficulty integrating data from various ongoing projects and programs and lack of monitoring of financial transactions to ensure there are no errors or fraud.